2012
DOI: 10.1111/j.1365-2648.2012.06012.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Being in it together’: living with a partner receiving deep brain stimulation for advanced Parkinson’s disease – a hermeneutic phenomenological study

Abstract: Spouses are deeply involved in their partners' illness and their experience of life is highly affected by their partners' illness, both before and after deep brain stimulation. The relationship is founded on solidarity and responsibility, which emphasizes spouses' need to be informed and involved in the process following Deep Brain Stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 28 publications
5
105
1
1
Order By: Relevance
“…The findings of this study highlight the centrality of occupation within individual and family member experiences of DBS for PD. The concept of broader treatment impacts, beyond symptom relief and motor improvement, has previously been identified in relation to DBS for PD (Haahr et al ., , , ; Hariz et al ., ). Similarly, recent literature has identified DBS can result in transitioning understandings of identity (Haahr et al .).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study highlight the centrality of occupation within individual and family member experiences of DBS for PD. The concept of broader treatment impacts, beyond symptom relief and motor improvement, has previously been identified in relation to DBS for PD (Haahr et al ., , , ; Hariz et al ., ). Similarly, recent literature has identified DBS can result in transitioning understandings of identity (Haahr et al .).…”
Section: Discussionmentioning
confidence: 99%
“…Medical management brings with it new routines for both the individual with PD and their carers. There develops an increasing focus on regularly timed medication in daily life and the need for rigid time keeping to maintain bodily control (Haahr, Kirkevold, Hall & Østergaard, ). The unpredictability of symptom fluctuations, accompanied by pain and changed body sensation and expression, affects functional tasks but also concepts of identity, confidence and connectedness (Haahr et al .).…”
Section: Introductionmentioning
confidence: 99%
“…Other qualitative studies showed (1) the severity of the disease and the functional status of the patient [19], (2) depression, disability, motor impairment, postural instability and cognitive impairment [20] and (3) nocturnal sleep disturbance, together with depressive symptoms and severity of motor symptoms, highly influence the QoL of patients [21]. Other qualitative studies have shown that the unpredictability of PD [22], the role of partners [23] and mental and psychosocial symptoms [24] highly influence the QoL of people with PD.…”
Section: Introductionmentioning
confidence: 98%
“…In PD, the process of psychosocial adaptation to the illness implies patients withstanding various changes to their social lives and as in their bodies (Fleming, Tolson, & Schartau, ; Haahr, Kirkevold, Hall, & Østergaard, , ; Stanley‐Hermanns & Engebretson ). Family carers, whose lives are influenced by the experience of their family member with PD, also find it difficult to adapt, due to the feeling of uncertainty to which the degenerative nature of PD gives rise and their lack of preparation for caring for a person with PD (Haahr, Kirkevold, Hall, & Østergaard, ; Portillo et al., ; Tan, Williams, & Morris, ). However, promoting the development of psychosocial adaptation to a LTC is positive, because this process can help the person adjust their activities and expectations to the new situation (Ambrosio et al., ; De Ridder, Geenen, Kuijer, & Van Middendorp, ; Stanton, Revenson, & Tennen, ).…”
Section: Introductionmentioning
confidence: 99%